Agrophysiology, biochemical, and yielding characteristics of Chinese cabbage due to formulations and concentrations of nutrient in hydroponic - Siahaan, Ferlist Rio; Tampubolon, Koko; Pardede, Erika (Comunicata Scientiae, 2023)
Hydroponic solution from agricultural organic waste can be used as an alternative to chemical solutions and strongly increases the growth and yield of Chinese cabbage plants. This study was to obtain formulations, concentrations, and their interactions that have the potential to increase the agronomic, physiological, biochemical, and yielding characteristics of Chinese cabbage in hydroponic culture. This study was conducted from September to November 2022 using a randomized block design with two factors and three replications. The first factor was the formulation of organic nutrient solutions (F1= banana peels+bean sprouts+eggshells; F2= banana humps+onion peels+bean sprouts+moringa leaves; F3= moringa leaves+onion peels+bean sprouts; F4= AB mix as a comparison). The second factor was the concentrations (600; 900; 1,200; 1,500 ppm). Data were analyzed using ANOVA and proceeded with the Duncan at P<0.05. The results showed that formulations F3 and F2 significantly increased Mg and chlorophyll b levels while formulation F1 increased nitrate and flavonoids. The concentrations ranged from 1,200 to 1,500 ppm showed the highest yield and shoot fresh weight were 2.86 kg m-2 year-1 and 30.70 g. The F3C4 interaction was highly recommended to increase the yield of Chinese cabbage by 2.68 kg m-2 year-1 compared to the other liquid organic fertilizers and it could be used as a substitute for using liquid chemical fertilizers in hydroponic culture.